ANTIOXIDANT ACTIVITY OF MOTHER-IN-LAW'S TONGUE (DRACAENA TRIFASCIATA (PRAIN) MABB.) LEAVES EXTRACT FROM FOUR DIFFERENT VARIETIES - Isnu Saputra, Dimas
Background and purpose: The mother-in-law's tongue plant is widely grown in Indonesia and has been used traditionally for various types of diseases. Exploration of secondary metabolite content and antioxidant activity of various varieties of mother-in-law's tongue is still limited. This study aims to determine antioxidant activity of ethanol extract from 4 varieties of Dracaena trifasciata, total phenolic content (TPC), flavonoid content (TFC), correlation of TPC and TFC to antioxidant activity, to identify and determine flavonoid compound in selected extract. Method: Samples were extracted by reflux using 96% and 70% ethanol solvents. Total phenol (TPC) was determined using Folin-Ciocalteu reagent, total flavonoid (TFC) by colorimetric reaction with AlCl3. Antioxidant activity was determined using the 2,2-diphenyl-1-picrylhydrazil (DPPH), Cupric Ion Reducing Antioxidant Capacity (CUPRAC), and Ferric Reducing Antioxidant Power (FRAP) methods. The correlation between TPC and TFC to antioxidant activity was analyzed using the Pearson method. Result: The highest TPC was shown by 96% ethanol leaves extract of D. trifasciata var. moonshine brazilian (138.534 ± 5.217 mg GAE/g) and the highest TFC in 96% ethanol extract of D. trifasciata var. gold flame leaves (368.957 ± 19.461 mg QE/g). The 96% ethanol extract of mediopicta cobra variety had highest antioxidant activities by DPPH and CUPRAC methods, while the highest antioxidant activity by FRAP method was shown by 70% ethanol extract of mediopicta cobra variety. TPC and TFC gave strong to very strong correlation with antioxidant activity. Conclusion: In general, 96% ethanol extract of D. trifasciata var. mediopicta cobra had higher antioxidant activity than the gold flame, moonshine brazilian, and banded nelsoni varieties. Phenol and flavonoid group contributed to antioxidant activity of four varieties of D.trifasciata tested. Rutin and kaempferol compounds were found in 96% ethanol extract and 70% ethanol extract of D. trifasciata var. mediopicta cobra leaves with concentration of 0.026 ± 0.002, 0.020 ± 0,002, and 0,071 ± 0,002, 0,052 ± 0,004 mg/g, respectively.